The Image Information Of Mri Brain In Axial Diffusion Weighted Image (Dwi) With Variation B Value In Ischemic Stroke - Siti Masrochah; Yeti Kartikasari; Ayu Mahanani (Universitas 'Aisyiyah Yogyakarta, 2020)
The purpose of the research is to identify the differences between image information of MRI Brain in axial plane Diffusion Weighted Image (DWI) sequence and variation b value in case ischemic stroke, and to determine optimal b value in examination MRI Brain in case Ischemic Stroke. This research was a quantitative research with experimental approach. This research was done in Panti Rapih Hospital, Yogyakarta and used 8 ischemic stroke patients with 3 variasion b value (500s/mm2, 1000 s/mm2, 1500 s/mm2) and 3 radiologists as respondents. The data were analyzed using Friedman test. Result showed that there was difference between image information of MRI Brain in axial plane Diffusion Weighted Image (DWI) sequence and variation b value in case ischemic stroke with p0.05 which means there is a difference between Basal Ganglia, Cerebellum, and the border of the infarction. Meanwhile, Cortex Cerebri, Thalamus and Pons obtained no difference in image information and the optimal b value for MRI Brain examination of ischemic stroke 1500 s/mm2. Based on the result there was a difference between image information of MRI Brain in axial plane Diffusion Weighted Image (DWI) sequence and variation b value in case ischemic stroke. Optimal value of variation b value for MRI Brain examination of ischemic stroke was 1500 s/mm2.